Effect of employee empathy on customer satisfaction and loyalty during employee–customer interactions: The mediating role of customer affective commitment and perceived service quality - Waseem Bahadur; Saira Aziz; Salman Zulfiqar (Cogent Business & Management, 2018)
This study investigates the indirect effect of employee empathy (EE) on customer loyalty (CL) and loyalty outcomes through intervening variables, i.e. customer affective commitment, perceived service quality, and customer satisfaction (CS). Associations between the constructs of the proposed model are examined in the context of employee–customer interactions. Data were collected through the online survey from 360 useable responses collected from active users of telecommunication services from the province of Anhui, China. To test the model, structural equation modeling was applied by using AMOS 21. The findings confirm the positive and indirect effect of EE on CL and loyalty outcomes (i.e. positive word-of-mouth and repurchase intentions). Results of the present study provide insights for the service sector, specifically telecommunication sector in order to increase CS and loyalty toward the services.
Keywords: 650